El procedimiento directo en el código orgánico integral penal y la vulneración del principio al debido proceso - Mena Pérez, Galo Patricio (2016)
While it is true that a country's development requires an efficient and effective justice, criminal law is very important because it regulates the punitive and preventive state exercise, because the purpose is not the criminalization of behaviors that harm legal rights if it contains and reduces the punitive power to guarantee the hegemony of the Rule of Law and Justice. With the creation of the Code of Criminal Integral (COIP) it has left behind nearly two centuries of changing offenses of which have contributed to improving gradually to the dynamics of Justice in Ecuador. The subject of this research, it relates to criminal law, where principles for the creation, interpretation and implementation to the enforcement of criminal laws is established, being very important to the performance of the punitive state apparatus, with the role of the judges and judges as guarantors of the rights of the parties involved in conflicts. Direct procedure is established in the Organic Code Integral Penal, which to be a process in which impairs a right to defense and due process, which is established in the Constitution of the Republic of Ecuador, as they violate rights hereunder. This judicial process should not only forewarn certain rights, since whereas the principles of simplification, immediacy, speed and procedural economy, the state through the Justice officials, such as the Council of the Judiciary and the Attorney General of the State to better do advise, or take refuge in the direct process without observing the other procedural part, processed subjects undergo this procedure without knowing who are defenseless or improper defense of a system of modern justice, thus affecting the application of due process. The structure of the final investigation report is as follows: Certification, Authorship, Thankful, Dedication, Table of Contents, Summary Castilian translated into English (Abstract) and Introduction; a) Conceptual Framework, includes the following: (concept of Law, Equity, Judgement, Procedure, Procedure Law, Administrative Procedure, Flagrancy, Judicial Resolution, Subject, effective judicial protection, due process, defense, right to defense, Test, punishable fact, Criminalization Crime); b) Setting Doctrinal (History of Law, Law, Criminal Law, Litigation, Direct Procedure in the Code of Criminal Integral); c) Legal Framework (Constitution of the Republic of Ecuador, Code of Criminal Comprehensive Organic Code of the Judiciary, Direct Procedure.)